APPLICATION OF ADVICE METHODS TO IMPROVING THE ABILITY TO PERFORM PRAYER IN CHILDREN AGED 5-6 YEARS OLD IN TK AISYIYAH BUSTANUL ATHFAL II PERUMNAS - Muzakkir; M. Yusuf T; Nurismi; Rismawati MS (Faculty of Tarbiyah and Teacher Training, 2022)
Stimulating six aspects of early childhood development is very important, especially in the aspect of religious values, especially in the achievement of developing worship. One way that can be done in improving the ability to do worship at an early age is to use the advice method. This service research aims to provide stimulation to aspects of children's value development in accordance with STTPA, namely to increase worship using the advice method at the age of 5-6 years. This community service research in the form of service learning was carried out at Aisyiyah Bustanul Athfal II Kindergarten Perumnas with a total of 4 children. The instrument used was an observation sheet and an evaluation of the implementation of the intervention. Data were analyzed using descriptive statistics. The results showed that the use of the advice method can improve the ability to do worship in children aged 5-6 years. The findings in this study imply that the advice method can be used for learning activities, especially in stimulating religious development.